2013
DOI: 10.1002/hed.23236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the significance of level IIb neck dissection for hypopharyngeal cancer

Abstract: The results suggest that preservation of level IIb during neck dissection was possible in N0 cases of hypopharyngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, Sakai et al, reporting the incidence of sublevel IIB metastases in patients with hypopharyngeal cancer, found involvement in 13.3% of the clinically positive necks and 0% of the clinically N0 necks. The authors concluded that sublevel IIB may be preserved during neck dissection in patients with clinically N0 hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sakai et al, reporting the incidence of sublevel IIB metastases in patients with hypopharyngeal cancer, found involvement in 13.3% of the clinically positive necks and 0% of the clinically N0 necks. The authors concluded that sublevel IIB may be preserved during neck dissection in patients with clinically N0 hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Level IIb lymph node pads may be left undissected so that spinal accessory nerve dysfunction is decreased and operative time reduced”. For hypopharyngeal cancer, Sakai et al 48 wrote: “The results suggest that preservation of level IIb during neck dissection was possible in N0 cases of hypopharyngeal cancer”.…”
Section: Clinical Behaviour and Natural Historymentioning
confidence: 99%